The effect of removing a dividing fence between two populations of black rhinos - Felix Patton; M.S. Mulama; S. Mutisya; P.E. Campbell (Pachyderm)
Ol Pejeta Ranching Limited in central Kenya was a 36,500 ha cattle ranch that included the 9,700 ha Sweetwaters Game Reserve, a sanctuary for black rhinos (Diceros bicornis). A change of ownership in 2004 led to an extension of the reserve to create Ol Pejeta Conservancy. By the end of 2006, the old reserve was reaching its Maximum Sustainable Yield of 45 rhinos, while at the beginning of 2007, 27 black rhinos were introduced into the new area. In order to reduce the density of rhinos in the old area, the fence dividing the two areas was removed, although opinions varied as to the likelihood of success of this action. Results of rhino movements between the two areas are presented. After 18 months, there was little movement of rhinos either from the old into the new area or from the new into the old area. Two sub-adult females were translocated from the old to the new area and settled close to their release sites.